Perceived Utility of Typesetting Homework in Post-Calculus Mathematics Courses. Issue 1 (2nd January 2016) - Quinlan, James; Tennenhouse, Craig
Abstract: Too often our students submit incomplete homework that is disorganized, unclear, and nonlinear. Typesetting with LATEX, although time consuming for those new to the software, strengthens communication by forcing organization and proper notation required by the precise, formal language of mathematics. In this manuscript we report on a study of 42 mathematics students who were required to typeset homework assignments using LATEX. Results show that the majority of students are comfortable using LATEX and agree that learning the markup language provides some useful benefits. Moreover, survey responses suggest that use of the software strengthens students' abilities to effectively communicate mathematically, but it is less likely to aid in understanding. We conclude with a discussion of practical tips for incorporating LATEX into undergraduate mathematics courses based on our experience and reflections.